Increased Knowledge of Seagrass Meadow Waters as an Economic and Sustainable Fishing ground for Small-Scale Bottom Gillnet Fisherman on Difur Beach Labetawi Village, Tual City - M. Picaulima, Simon; D. Rahakbauw, Siska; K. Ngamel, Anna; C. Ohoiwutun, Elisabeth; Kilmanun, Anthon D. (Agrikan Jurnal Agribisnis Perikanan, 2023)
Seagrass beds are coastal ecosystems with greater catch productivity than coral and mangrove ecosystems. This is what makes seagrass beds a very economical fishing ground. Still, the high fishing activity in seagrass beds has yet to ensure the sustainability of fish resources of economic value. Therefore, increasing knowledge and understanding of bottom gillnet fishermen who make seagrass meadows an economical and sustainable fishing ground is necessary. The counseling activity was conducted on September 16, 2023, on Difur Beach Labetawi Village, Tual City, and 12 small-scale bottom gillnet fishermen attended. Data were collected using questionnaires to evaluate the level of knowledge and understanding before and after material delivery and analyzed by descriptive methods. The counseling results show that most small-scale bottom gillnet fishermen need help understanding seagrass ecosystems as economic fishing grounds in coastal areas. the results of the evaluation of participants show an increase in knowledge and good understanding from fishermen. Therefore, these changes are expected to affect fishermen's behavior in fishing activities to ensure the sustainability of economically important fish resources in seagrass fishing grounds in the future.